Portuguese National Pedagogical Plan for Anesthesiology Residents' Evaluation: The Participants' Rating - Matos,Francisco Maio (2022)
Abstract Introduction: Simulation in anesthesiology has been considered a crucial complementary training for residents of this medical specialty. A National Pedagogical Plan of the Biomedical Simulation Center from Centro Hospitalar e Universitário de Coimbra was designed according to the curricular objectives defined by the Portuguese Board of Anesthesiology. The objective of this study is to analyze the evaluation of the programmatic contents included in the simulation courses from the participants' point of view. Methods: Post-course confidential questionnaires were answered by all the anesthesiology residents that attended the different modules. All the questions were answered on a 0-10 scale. This study was conducted at the Biomedical Simulation Center from Centro Hospitalar e Universitário de Coimbra, Portugal, from February 2011 to March 2018. Results: A total of 344 questionnaires were answered. The students considered that all the topics included in the simulation courses are important for the training during residency, being basic pharmacology in anesthesiology (Year I) the less important one being classified with 5.03 (IC 95% 4.83-5.22). All the programmatic contents included in the simulation module of the year IV were classified by the residents with importance higher than 8. This last year was the one where the importance of the topics is all numerically higher than in the other years. Conclusion: Given the importance attributed by the residents to the programmatic content included in the simulation courses, we can conclude that the design of the courses was appropriate to the needs and the goals of the anesthesiology residents, as a complement of their internship.